Analisis Budaya Kerja dan Fokus Pelanggan dalam Meningkatkan Kualitas Produk CV Digital Printing - Komariyah, Imas; Ismawanti, Resty (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2025)
This study is motivated by the importance of improving product quality as a key factor in maintaining a company’s competitiveness in the digital printing industry. One of the main determinants of product quality improvement lies in the work culture and customer focus implemented within the organization. CV Digital Printing, as a company engaged in printing services, must ensure that both aspects function effectively to produce products that meet customer needs and expectations. However, based on preliminary observations, inconsistencies were found in the implementation of work culture, as well as suboptimal long-term relationships with customers, which affect the quality of production outcomes. The research problems formulated in this study are: (1) How are the work culture, customer focus, and product quality at CV Digital Printing? (2) To what extent do work culture and customer focus partially and simultaneously influence product quality? The research method used is quantitative with an associative–verificative approach. Data were collected through questionnaires distributed to employees of CV Digital Printing and analyzed using path analysis with the help of SPSS version 26. Validity, reliability, and normality tests were conducted to ensure the accuracy and feasibility of the research model. The results of the study show that, descriptively, work culture, customer focus, and product quality are categorized as fairly good, indicating room for improvement. Verificatively, work culture and customer focus have a positive and significant effect on product quality, both partially and simultaneously. The combination of a conducive work culture and strong customer focus creates a positive synergy that contributes to the improvement of product quality and the company’s competitiveness.